Effects of Input- and Output-based Planning on Korean College Students’ Communication Strategy and Speaking Anxiety - Lee, Dongju; Kim, Sung-Yeon (Journal of Asia TEFL, 2018)
This study examined the effects of input- and output-based planning on Korean college students' communication strategy use and speaking anxiety. Two groups of 84 Korean female college students (n=168) have participated in the study, with one group performing reading activities, and the other performing writing activities prior to speaking tasks. The findings of the study indicate that the two groups did not show any meaningful differences in their overall communication strategy use. However, significant differences were found between the groups in light of social-affective strategies and meaning negotiation strategies. Particularly notable is that these strategies were utilized to a greater extent by the writing group, compared to its counterpart, i.e., the reading group. In contrast, the effects of different types of planning were found to be nonsignificant for speaking anxiety. In other words, both groups showed similar levels of speaking anxiety, regardless of planning conditions, although their anxiety decreased over time as a result of strategic planning. These findings bear meaningful implications for the role of strategy training for language learners and for the importance of creating optimal conditions to maximize effectiveness of learning.